2020
DOI: 10.1155/2020/3808036
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage by Staphylococcus aureus among Healthcare Workers and Students Attending a University Hospital in Southern Brazil: Prevalence, Phenotypic, and Molecular Characteristics

Abstract: Background. Staphylococcus aureus can asymptomatically colonize the human anterior nares and skin, and nasal colonization by this bacterium represents a potential risk for development of invasive infections. The aim of this study was to determine the prevalence of S. aureus nasal carriage among healthcare workers and students attending a university hospital and to characterize the isolates phenotypically and molecularly. Methods. A cross-sectional study was performed with 324 volunteers. Cultures from nasal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…One of the encouraging results in our study is that, all isolates were sensitive to rifampicin and vancomycin, which is in line with studies in Nepal 29 and Southern Brazil, 24 suggesting these two drugs are still useful and effective for managing S. aureus and MRSA-related infections. Although the source population was different, a recent study in North Ethiopia also indicated the absence of resistance to these drugs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One of the encouraging results in our study is that, all isolates were sensitive to rifampicin and vancomycin, which is in line with studies in Nepal 29 and Southern Brazil, 24 suggesting these two drugs are still useful and effective for managing S. aureus and MRSA-related infections. Although the source population was different, a recent study in North Ethiopia also indicated the absence of resistance to these drugs.…”
Section: Discussionsupporting
confidence: 89%
“…The 78.2% penicillin resistance in this study was comparable with the 71% resistance reported in the Netherlands 22 but lower than two former studies done in Dessie and Adigrat, Ethiopia (100% resistant) 19 , 23 and 90.6% to 100% in Southern Brazil and Gaza. 21 , 24 The rate of multidrug-resistance was similar to reports from Dessie and Jimma, Ethiopia. 23 , 25 …”
Section: Discussionsupporting
confidence: 80%
“…Resistance to mecA has been correlated with the presence of the mecA gene for a long time. On the other hand, where resistance to oxacillin is concerned, the presence of S. aureus isolates positive for mecA but phenotypically susceptible to oxacillin (OS-MRSA) has been reported, including in Brazil (Guimarães et al ., 2017; Danelli et al ., 2020). These latter authors found strains of OS-MRSA in the nasal cavity of about 2000 health professionals and students from a university hospital in southern Brazil, raising an alert about the fact that these strains can be mistakenly identified as S. aureus sensitive to methicillin (MSSA) by phenotypic methods routinely used in most clinical laboratories, which would pose a threat to the treatment of staphylococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. aureus has been a known pathogen for a long time, isolates of methicillin-resistant S. aureus (MRSA) have been found since the 1980s, being responsible for hospital-acquired infections and showing the capacity to resist various antimicrobials. Currently, it has become a worldwide pathogen related to the community and food transmission (Gonzalez et al, 2017). The antimicrobial resistance capacity of S. aureus is the result of several factors, which include the production of β-lactamases (encoded by the blaZ gene) and alteration of the binding site for β-lactam antibiotics due to the production of an additional penicillin-binding protein present in methicillin-resistant strains of S. aureus (Song et al, 2016;Chen et al, 2017).…”
mentioning
confidence: 99%
“…A previous study carried out in the USA estimated that around 32.4% of the population were colonized with S. aureus but the prevalence of methicillin-resistant strains in the isolates was estimated to be 0.84% for the same population [ 72 ]. However, a higher percentage of methicillin-resistant strains has been found to be nasally carried by healthcare workers [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%